The Impact of Psoas Muscle and Pelvis Anatomy on Lateral Lumbar Interbody Approaches. (16th November 2020) - Abu-Rmaileh, Muhammad; Thomas, Kevin; Afuwape, Olusoji A; Kazemi, Noojan
Abstract: INTRODUCTION: Lateral lumbar interbody fusion (LLIF) is a less disruptive approach to the lumbar spine that allows for decompression and reconstruction of the intervertebral disk. Despite minimizing damage, this approach risks damage to the lumbar plexus during the operative traverse of the psoas muscle. We propose that pelvic anatomy variations can render the previously-defined operative safe-zones unsafe and have significant impact on surgical access. METHODS: We reviewed imaging on 99 consecutive patients (42 M; 57 F) that underwent LLIF at our institution. We categorized patients based on 3-feet standing x-rays and preoperative MRI, assessed for position of the iliac crest and percentage obscuration with respect to the L4/5 disc space. We further classified the location of both the L3 and L4 nerve roots into 4 equidistant zones along the AP axis of the disc spaces well as anterior/posterior subzones in Zones 1 and 2. The distance between the anterior aspect of the psoas (ATP) and closest great vessel was measured as well. Pelvis types were assessed for ability to perform the 'orthogonal maneuver' in the ATP approach. RESULTS: 52% of the male subjects compared to 33% of female subjects had an iliac crest above the L4 pedicle on lateral xray. The percent obscuration of the L4/5 disc space by the iliac crest revealed a binary distribution with the majority of L4/5 disc space either completely obscured or completely visible allowing full lateral access. 95% of the L4 nerve root was found in zone 1, while the L3 nerve root was more heterogeneous in location. The average distance between psoas muscle and the vessel was 16.25mm implying binary ability to perform the ATP approach in most cases. The gynecoid and android pelvis were the most and least favorable pelvis types respectively in performing the ATP orthogonal maneuver. CONCLUSION: Understanding psoas and pelvic anatomy plays a critical role in determining optimal operative approach for lateral and ATP interbody fusion.